Acidic pH-responsive polymer nanoparticles as a TLR7/8 agonist delivery platform for cancer immunotherapy. Issue 44 (7th November 2018) - Kim, Hyunjoon; Sehgal, Drishti; Kucaba, Tamara A.; Ferguson, David M.; Griffith, Thomas S.; Panyam, Jayanth
Abstract : Acidic-pH responsive PLGA NPs enhance endo/lysosomal delivery of the TLR7/8 agonist and elicit a stronger anti-tumor T cell response than conventional PLGA NPs. Abstract : Synthetic imidazoquinoline-based toll-like receptor (TLR) 7/8 bi-specific agonists are promising vaccine adjuvants that can induce maturation of dendritic cells (DCs) and activate them to secrete pro-inflammatory cytokines. However, in vivo efficacy of these small molecule agonists is often hampered by their fast clearance from the injection site, limiting their use to topical treatments. In this study, we investigated the use of acidic pH-responsive poly(lactide- co -glycolide) (PLGA) nanoparticles for endo–lysosome specific release of 522, a novel TLR7/8 agonist. Bicarbonate salt was incorporated into the new formulation to generate carbon dioxide (CO2 ) gas at acidic pH, which can disrupt the polymer shell to rapidly release the payload. Compared to conventional PLGA nanoparticles, the pH responsive formulation resulted in 33-fold higher loading of 522. The new formulation demonstrated acid-responsive CO2 gas generation and drug release. The acid-responsive formulation increased the in vitro expression of co-stimulatory molecules on DCs and improved antigen-presentation via MHC I, both of which are essential for CD8 T cell priming. In vivo studies showed that the pH-responsive formulation elicited stronger antigen-specific CD8 T cell and natural killer (NK) cell responses than conventional PLGA nanoparticles, resulting in enhanced anticancer efficacy in a murine melanoma tumor model. Our results suggest that acidic-pH responsive, gas-generating nanoparticles are an efficient TLR7/8 agonist delivery platform for cancer immunotherapy.